2011
DOI: 10.3390/s110505290
|View full text |Cite
|
Sign up to set email alerts
|

Odour Detection Methods: Olfactometry and Chemical Sensors

Abstract: The complexity of the odours issue arises from the sensory nature of smell. From the evolutionary point of view olfaction is one of the oldest senses, allowing for seeking food, recognizing danger or communication: human olfaction is a protective sense as it allows the detection of potential illnesses or infections by taking into account the odour pleasantness/unpleasantness. Odours are mixtures of light and small molecules that, coming in contact with various human sensory systems, also at very low concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
150
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 198 publications
(151 citation statements)
references
References 146 publications
(190 reference statements)
0
150
0
1
Order By: Relevance
“…[1][2][3] In particular, odor analysis can provide valuable information on food quality and safety, which is especially welcome when achieved by simple, rapid, on-line and real-time detection methods. Thus, volatile organic compounds (VOCs) involved in food metabolic pathways (carboxylic acids, alcohols, carbonyl compounds, lactones) or food ripening (terpenes, esters, ethers) contribute significantly to agreeable flavors.…”
Section: ■ Introductionmentioning
confidence: 99%
“…[1][2][3] In particular, odor analysis can provide valuable information on food quality and safety, which is especially welcome when achieved by simple, rapid, on-line and real-time detection methods. Thus, volatile organic compounds (VOCs) involved in food metabolic pathways (carboxylic acids, alcohols, carbonyl compounds, lactones) or food ripening (terpenes, esters, ethers) contribute significantly to agreeable flavors.…”
Section: ■ Introductionmentioning
confidence: 99%
“…This method also takes into account the odour mixture as a whole, so it is not able to distinguish individual chemical compounds [15]. It was also found that odour assessment results can be affected by psychological aspects of panellists too, because in some cases the panellists tend to guess the correct result instead of impartial assessment [16].…”
Section: Dynamic Olfactometrymentioning
confidence: 99%
“…This signal is conducted by nerve fibres to the olfactory centre in brain where it is evaluated. The evaluation is done in such a way that the received signal is compared to information stored in memory [15]. As a result, the human knows which odour he or she smells (or which of the known odours this sensed odour resembles the most) and whether this odour is pleasant or not.…”
Section: Electronic Nosementioning
confidence: 99%
“…The second sample was taken after one hour. Samples were taken at a height of several centimetres from the waste or building debris surface with the vacuum chamber AC'SCENT and collected to Tedlar bags of 10 dm 3 capacity and analysed in a laboratory on the same day [19]. The analysis was performed by the method of forced selection.…”
Section: Methodsmentioning
confidence: 99%